EFEKTIVITAS PENYALURAN RASKIN DI KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Andri "; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Raskin is one of teh social protection program, that means is to meet the needs of food (rice), which is expected to reduce the expulsion of poor households. Raskin began since 1998. The financial crisis of 1998 was the beginning of the implementation of Raskin program which that means to strengthen the resilience of domestic programs, especially poor households. Was originally called Program Special Market Operation (OPK). And then in 2002 was converted into a program Raskin. In distribusion households targeted beneficiaries will receive 15 Kg/RTS-P/mounth with teh price Rp. 1.600/Kg at the distribution points. In fact the distribution of Raskin is not always fully guided in government policy as outlined in the general guidelines Raskin 2014. Researchers took special location in the district Kerumuta of Pelalawan regency. The mean .this study was determine the factors that influence the effectiveness of the distribution of Raskin.This research use qualitative descriptive method. Data accumulation to do with observation method and deepen interview from various informant who already determined. The qualitative research, data retrivied from primary and secunder source. In analysis of data, all information that collected must studied until can withdrawn a conclusion be one unity thet complete, that is result of research. The teory concept thet used is Steers teory about factor that influence of effectiveness.The result of this research was concluded that effectiveness of Raskin distribution in Kerumutan district Pelalawan Regency assessed less effective because not achievement of target 6 T, that is exact of target, amount, price, time, administration and quantity. Then, factor that influence of effectiveness Raskin distribution are employee or executor factor that review from availability human resource and wisdom management practices factor that review from strategy and accupation mechanism of Raskin distribution.Keyword: Raskin effectiveness, Raskin program, factor that influence of effectivenes.